Is Article 16(3) of the Model Law a ‘one-shot remedy’ for non-participating respondents in international arbitrations? - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2018)
It is not uncommon for practitioners acting for claimants in an arbitration to encounter a respondent who chooses to boycott the arbitral process. In cases involving such “non-participating” respondents, what are the rights and obligations of each party? Specifically, insofar as Model Law jurisdictions are concerned, if a tribunal decides on jurisdiction as a preliminary issue must the non-participating respondent apply under Article 16(3) of the UNCITRAL Model Law on International Commercial Arbitration (Model Law) to the curial Court to review that decision, or otherwise lose the right to challenge any eventual award thereafter on jurisdictional grounds? Can the non-participating respondent surface at a later stage to set aside, or alternatively resist enforcement, of any eventual award based on jurisdictional grounds?